-7x-15+9x+23=2

Simple and best practice solution for -7x-15+9x+23=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-15+9x+23=2 equation:


Simplifying
-7x + -15 + 9x + 23 = 2

Reorder the terms:
-15 + 23 + -7x + 9x = 2

Combine like terms: -15 + 23 = 8
8 + -7x + 9x = 2

Combine like terms: -7x + 9x = 2x
8 + 2x = 2

Solving
8 + 2x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 2x = 2 + -8

Combine like terms: 8 + -8 = 0
0 + 2x = 2 + -8
2x = 2 + -8

Combine like terms: 2 + -8 = -6
2x = -6

Divide each side by '2'.
x = -3

Simplifying
x = -3

See similar equations:

| r/2=11/8 | | 10b-2=4b-14 | | -(5x-10)=5 | | -5+2x-7x=35 | | a=160m+215 | | 4x-22=2x+12 | | -4m+2+1m=23 | | 2p-3=7 | | 15m+4-9m= | | -3x-7x=97 | | 6x+6=-x+55 | | 0.5=0.4y-0.25y | | 2x+6=4x+12 | | 3(-3x-2)-4x-5=-3 | | 5x-2x=168 | | .4(x-12)=1.2(x-4) | | 2(3a-4.2)=5a | | 6g-9/3=g | | 4(m+1)-2(3m+1)=-3(m-7)+5 | | z-2/3=1/8 | | 3(s+1)-5=3s-2 | | 5x-27=-4x | | -4-5x=7-x | | 5x+9+8=4 | | 2.85s-7=12.85s-2 | | ax+by=c(y) | | 2(x+5)+3= | | 2.5(x-2)-6=9 | | -2x-9=3x+4 | | b-31=-63 | | 4(2s-1)=-8(.5-s) | | 17+n=21 |

Equations solver categories